Penurunan Tarif PPh Badan Sebagai Ketidakpastian Eksternal dan Tax Avoidance - Milla Sepliana Setyowati; Mutya Nurmala Raya (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to investigate the effect of changes in corporate income tax rates as the company's external uncertainty on tax avoidance, which changes make companies engage in tax avoidance practices to ensure future benefits and to increase value. Using agency theory as the basis for analyzing, this study uses a quantitative approach and processes data using a linear regression method with a sample of consumer non-cyclical industry companies for the 2018-2020 period. The processed results show that external uncertainty does not positively affect avoidance. Changes in tax policy make the tax system uncertain for companies, causing managers to engage in tax avoidance. Fluctuating tax rates will affect the company's tax benefits and tax burden in the future, so companies tend to carry out tax planning aggressively that is carried out intensely and will be more inclined to tax avoidance. This research has implications for the government's considerations in making adjustments or policy changes that will make the tax avoidance gap even bigger for business people. Therefore, it is necessary to support to prevent an increase in tax evasion as an opportunistic business actor. In addition, this study also contributes theoretically and literature on the relationship between external uncertainty, the uncertainty of tax benefits, agency, and tax avoidance. The novelty offered in this study is to analyze the effect of changes in the policy on reducing corporate income tax rates that occurred in Indonesia due to the covid-19 pandemic as an external uncertainty on tax avoidance behavior.